Leadership Function and Job Satisfaction on Organizational Citizen Behavior (OCB) with Readiness to Change as an Intervening Variable - Ernawati, Rini; Pamungkas, Rian Adi; Anindita, Rina (Alta Dharma Publisher, 2025)
Background: This study is based on the results of initial observations that inform the number of patient complaints related to the quality of service from patients in 2023. Objective: The purpose of this study is to empirically reveal the influence of leadership function and job satisfaction on OCB with readiness to change as an intervening variable. Method: This research was conducted at a type B private hospital in Tangerang City. The research was carried out in the period May – June 2024. The type of research is included in the quantitative with a cross sectional study design. The population used is nurses with permanent employee status. The sampling technique uses non-probability, with a calculation that multiplies the number of indicators by 5 observations, so that the number of samples is 180 respondents. The data collection technique uses a questionnaire, and the analysis method uses the three-box method and SEM analysis. Result: The results of the analysis prove that the leadership function and readiness to change are influential to OCB with readiness to change as an intervening variable, leadership function and job satisfaction are dependent on readiness to change and OCB, leadership function, job satisfaction and readiness to change have an effect on OCB. Readiness to change is the dominant variable that is able to increase OCB with a coefficient of 0.71